Trends in trauma transfusion - Bhananker, Sanjay M (Medknow Publications Pvt Ltd, 2011)
Trauma is the leading cause of death in young adults and acute blood loss contributes to a large portion of mortality in the early post-trauma period. The recognition of lethal triad of coagulopathy, hypothermia and acidosis has led to the concepts of damage control surgery and resuscitation. Recent experience with managing polytrauma victims from the Iraq and Afghanistan wars has led to a few significant changes in clinical practice. Simultaneously, transfusion practices in the civilian settings have also been extensively studied retrospectively and prospectively in the last decade. Early treatment of coagulopathy with a high ratio of fresh frozen plasma and platelets to packed red blood cells (FFP:platelet:RBC), prevention and early correction of hypothermia and acidosis, monitoring of hemostasis using point of care tests like thromoboelastometry, use of recombinant activated factor VII, antifibrinolytic drugs like tranexamic acid are just some of the emerging trends. Further studies, especially in the civilian trauma centers, are needed to confirm the lessons learned in the military environment. Identification of patients likely to need massive transfusion followed by immediate preventive and therapeutic interventions to prevent the development of coagulopathy could help in reducing the morbidity and mortality associated with uncontrolled hemorrhage in trauma patients.